KONSERVATISME AKUNTANSI, GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA EARNINGS RESPONSE COEFFICIENT - Wulandari, Ida Ayu; Herkulanus, Bambang Suprasto (E-Jurnal Akuntansi, 2015)
Earnings Response Coefficient is one method that is often used to measure the quality of earnings . The higher the ERC , the earnings quality is getting better . Earnings quality will not mislead users of financial statements information in making decisions . This study uses two factors suspected to affect the quality of earnings that accounting conservatism and good corporate governance because these two factors can be the solution of the conflict in the enterprise agency . In addition, this study also examines the factors affecting the market response to earnings information in addition to the quality of earnings as investors not only need profit information but also other information one of which is the disclosure of Corporate Social Responsibility ( CSR )
Keywords: good corporate governance, ERC, accounting conservatism, CSR.